Karekteristik Lumpur Ipal Kota Jambi Sebagai Bahan Campuran Material Konstruksi - Qolbi, Muhammad Khofidul; Rosidawani, Rosidawani; Adhitya, Bimo Brata (Universitas Batanghari Jambi, 2025)
Jambi City IPAL is a new construction which is a container for processing Jambi City's domestic waste. The source of the sludge comes from household wastewater in Jambi City. The sludge produced from the Jambi city wastewater treatment process (IPAL) is dark brown in color and the sludge is floc in nature. District is mud whose grains are separated without coagulants, generally this mud contains sand, grit and small gravel fragments. Mud in the form of floc, namely (chemiflocc) is very large in volume, especially in WWTPs. The XRF results of WWTP mud show high levels of SiO2 and Al2O3, namely 61.56% and 26.93% respectively. The elements contained in cement are found in WWTP mud such as SiO2, Al2O3, Fe, CaO, K2O, MgO, and Na2O. If compared, WWTP mud has the same properties as cement. XRD test results show crystal phase conditions show peaks with the highest count value at the position [o2Theta] 26.701OH. The SEM mud results show that the grains are in the form of fragments like irregular lumps with varying grain sizes. This condition shows that dry mud has good binding capacity. Jambi City WWTP waste sludge from XRF results has a mineralogical composition similar to cement, because it contains main oxides such as SiO2, Al2O3, CaO, and Fe. Based on its chemical composition, waste sludge has the potential to be used in the production of construction materials after being subjected to combustion treatment.